Vigilancia de la salud de los trabajadores: el pendiente desarrollo de una mayor regulación en el Perú - Castro Ramos, Trinidad (2024)
The purpose of this article is to present the regulation of health surveillance of employees in Peru. As well as parameters from other countries that may be useful to develop and/or complement the guidelines already established in the Law, Regulation and Protocol of Occupational Safety and Health. This in the context, no less important, of Safety and Health at Work as a Fundamental Right for the International Labor Organization, which emphasizes the relevance of greater protection to health surveillance, the promotion of work adaptation and participation in the analysis of occupational accidents and occupational diseases.